PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) MENGGUNAKAN APLIKASI KVISOFT FLIPBOOK MAKER PADA MATA PELAJARAN EKONOMI - Sahila Disti Safira El Tsani; Retno Mustika Dewi (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This development research aims to develop Electronic Student Worksheets (E-LKPD) using the Kvisoft Flipbook Maker application in Economics Subjects, analyze feasibility, analyze learning outcomes and analyze student responses to Electronic Student Worksheets (E-LKPD) using the application Kvisoft Flipbook Maker on Economics Subjects. This R&D research uses a 4D model with define, design, develop, and disperse stages. The research subjects were students of class XI IPS 3 at SMAN 15 Surabaya. The results of the validity of the experts obtained a feasibility average recapitulation of 92.52% with a very feasible interpretation. The score obtained from material experts was 93.39% with very proper interpretation, 87.27% for linguists with very feasible interpretation, and 96.92% for media experts with very proper interpretation. The effectiveness of student learning outcomes gives an effective influence and the student's response to the product shows the criteria are very well understood with a proportion of 93.62%. The conclusions obtained refer to the results of the study that this teaching material is very suitable for use as a learning resource for students.